Traffic scheduling for deep packet inspection in software‐defined networks. (12th October 2016) - Huang, Huawei; Li, Peng; Guo, Song
Summary: Deep packet inspection (DPI) is important for network security. In this paper, we consider a software‐defined network where several DPI proxy nodes are available for serving flows from ingress switches. These DPI proxy nodes can be implemented in either software or hardware. We study an integrated proxy allocation and routing determining problem with the objective of minimizing the total delay of flows from ingress switches to DPI proxies. This problem is formulated as an integer linear programming problem that is NP‐hard in general. To solve this problem, we design a 2‐phase algorithm that can quickly select proxy and find routing paths for incoming flows. Finally, extensive simulations are conducted to evaluate the performance of our proposed algorithm. Some useful parameter setting insights are obtained.